Evidence of bacterial imprints in different types of non-struvite kidney stones - Felix Grases; Antonia Costa-Bauzá; Francesca Julià; Bernat Isern; Jordi Guimerà; José Luis Bauzá-Quetglas; Valentí Tubau; Enrique Pieras (BMC Urology)
Abstract Background Recent studies of renal lithiasis identified bacterial imprints in apatite phosphate stones and mixed calcium oxalate/apatite phosphate stones, neither of which contained struvite. Methods This cross-sectional observational study examined 903 stones that were collected from 844 patients during the course of 1 year. All stones were initially examined by stereoscopic microscopy. Stone fragments were then examined by scanning electron microscopy + microanalysis by X-ray dispersive energy and by Fourier-transform infrared spectroscopy. When bacterial imprints were detected, biochemical and bacteriological analysis of the patient’s urine was performed. Results We found 8 renal stones that had bacterial imprints but no struvite. All 8 stones contained hydroxyapatite, and the imprints were located in this region. Five stones contained hydroxyapatite as the major component, two stones were mixed hydroxyapatite/calcium oxalate dihydrate stones, one was a papillary calcium oxalate monohydrate stone in which bacterial imprints were located at Randall’s plaque and the other was a cavity calcium oxalate monohydrate stone that contained hydroxyapatite in the central core with bacterial imprints. Conclusion We identified bacterial imprints in different types of renal stones that lacked struvite, including papillary stones, and these imprints were always present in a hydroxyapatite matrix. Notably, a urinary pH above 6.0 favors the formation of apatite phosphates and the growth of bacteria. Our findings point to the importance of controlling urinary pH to prevent bacteria-mediated calculogenic processes. Clinical trial number Not applicable.